2000
DOI: 10.1093/molehr/6.12.1069
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of the human YWK-II gene, encoding a sperm membrane protein related to the Alzheimer betaA4-amyloid precursor protein

Abstract: The YWK-II cDNA, RSD-2, encoding a sperm membrane protein was isolated from a rat testis cDNA expression library. Using the RSD-2 insert in combination with rapid amplification of cDNA ends (RACE), the corresponding human gene was isolated from a human testis cDNA expression library. The human testis cDNA, HSD-2, is 3654 bp in length and contains an open reading frame of 763 codons. Hydropathicity analysis showed that the deduced polypeptide is a single strand transmembrane protein. The deduced polypeptide has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Apart from the previously demonstrated binding of YWK-II protein to both rMIS and G o protein (Huang et al, 2000;Tian et al, 2001), the present study has provided further evidence of the involvement of YWK-II protein in MIS-activated and G ocoupled ERK signaling pathways as well as in mediating the effect of MIS on cell survival in a CHO model and mouse sperm in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Apart from the previously demonstrated binding of YWK-II protein to both rMIS and G o protein (Huang et al, 2000;Tian et al, 2001), the present study has provided further evidence of the involvement of YWK-II protein in MIS-activated and G ocoupled ERK signaling pathways as well as in mediating the effect of MIS on cell survival in a CHO model and mouse sperm in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 56%
“…The ovary-derived CHO cell is similar to the sperm in that it produces G o protein (Vanhauwe et al, 2002) (Huang et al, 2000), and others have shown that this G protein is connected to the ERK cascade (Kim et al, 2003). Therefore, YWK-II protein, as a receptor for MIS, may be coupled to G o protein to activate ERK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F11 cells, the hybrid cells of a rat embryonic day 13 (E13) primary cultured neuron and a mouse neuroblastoma, were grown in Ham's F-12 (Life Technologies, Gaithersburg, MD) plus 18% fetal bovine serum (FBS) (Hyclone, L ogan, UT) and antibiotics, as described previously (Platika et al, 1985;Yamatsuji et al, 1996;Huang et al, 2000;Niikura et al, 2001). F11 cells (7 ϫ 10 4 cells per well in a six-well plate cultured in Ham's F-12 plus 18% FBS for 12-16 hr) were transfected with plasmids encoding FAD genes by lipofection [1 g of FAD cDNA, 2 l of LipofectAM I N E, and 4 l of PLUS reagent (Life Technologies)] in the absence of serum for 3 hr and were incubated with Ham's F-12 plus 18% FBS for 2 hr.…”
Section: Methodsmentioning
confidence: 99%
“…F11 cells are the hybrid of a rat embryonic day 13 primary cultured neuron with a mouse neuroblastoma NTG18 and have so far been used as the best model for primary neurons (Yamatsuji et al 1996;Storms and Rutishauser 1998;Ghil et al 2000;Hagiwara et al 2000;Hashimoto et al 2000aHashimoto et al ,b, 2001aHashimoto et al ,b,c, 2003aHashimoto et al , 2004aHuang et al 2000;Sudo et al 2000Sudo et al , 2001Niikura et al 2001). F11 cells overexpressing L401K p75NTR (F11/L401K cell) were established as follows.…”
Section: Genes and Chemical Materialsmentioning
confidence: 99%